Fragmentasi Peledakan Batuan dengan Metode Image Analysis dan Perhitungan Teoritis Pada Pit Tempudo 6 PT. Indexim Coalindo Kabupaten Kutai Timur, Provinsi Kalimantan Timur - Rafael Bonardy Gultom; Tommy Trides; Albertus Juvensius Pontus; Oktaviani, Revia; Harjuni (Retii, 2023)
The research was conducted at PT. Indexim Coalindo is a coal mining company operating in East Kalimantan. The mining method used is an open pit with the main activity of spreading the overburden being blasting. Fragmentation is an important factor in blasting for this company the fragmentation size does not exceed 86 cm or ≤ 20% based on the bucket width of the loading digging tool, namely the Komatsu PC 2600. The method used to analyze the fragmentation resulting from blasting is actual Image Analysis, and theoretically uses the Kuz-Ram method. This is intended to determine and compare the percentage distribution of fragmentation sizes resulting from blasting. Results from fragmentation analysis of PT. Indexim Coalindo in the field carried out in July 2023 and August 2023. In this case, it shows that the image analysis method results in a smaller fragmentation size than the Kuzram method and is in line with the target that the company standards want to produce.